Breastfeeding and respiratory, ear and gastro-intestinal infections, in children, under the age of one year, admitted through the paediatric emergency departments of five hospitals - Branger, Bernard; Bainier, Amaïa; Martin, Laureen; Darviot, Estelle; Forgeron, Aude; Sarthou, Laurent; Wagner, Anne-Claire; Blanchais, Thomas; Brigly, Thomas; Troussier, Françoise (Frontiers in Pediatrics, 2023)
Background Breastfeeding is a protective factor against respiratory and intestinal infections in developing countries. In developed countries, proof of this protection is more difficult to show. The objective of the study is to compare the proportion of children breastfed during their first year in groups of children with infectious pathologies supposedly prevented by breastfeeding and children free of these infectious pathologies. Method Questionnaires about diet, socio-demographic data and the motive for consultation were given to the parents upon arrival in the paediatric emergency departments of 5 hospitals located in Pays de Loire (France) in 2018 and 2019. Children with lower respiratory tract infections, acute gastroenteritis and acute otitis media were included in the case group (A), children admitted for other reasons were included in the same control group (B). Breastfeeding was classified as exclusive or partial. Results During the study period, 770 infants were included, of which 273 (35.5%) in group A. In this group, children were significantly less breastfed on the day of admission than children in group B : for example, children under 6 months, 23.1% versus 37.2%; odds ratios (OR = 0.51 (0.33 - 0.78); p = 0.002). Similar results were found at 9 and 12 months. Multivariate analysis confirmed the same results with an aOR = 0.62 (0.39 - 0.98) (p=0.042) at 6 months, as well as at 9 and 12 months for breastfeeding and exclusive breastfeeding. Sensitivity analyses (age-matching, analysis by type of infection) found the same protection for breastfeeding for over 6 months. Conclusion Breastfeeding is a protective factor against respiratory, gastrointestinal and ear infections when pursued at least 6 months after birth. Other factors such as collective childcare, pacifiers and parental professional status can reduce the protective effect of breastfeeding.